2012
DOI: 10.3402/ehtj.v5i0.10904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of power frequency electromagnetic fields on melatonin and sleep in the rat

Abstract: BackgroundStudies investigating the effect of power frequency (50–60 Hz) electromagnetic fields (EMF) on melatonin synthesis in rats have been inconsistent with several showing suppression of melatonin synthesis, others showing no effect and a few actually demonstrating small increases. Scant research has focused on the ensuing sleep patterns of EMF exposed rats. The present study was designed to examine the effects of extremely low power frequency electromagnetic fields (EMF) on the production of melatonin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Reactogenic vaccines are reported to produce oxidative stress [ 19 ]. Radiation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], as well as pesticides [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] (and solvents [ 52 , 53 ]), can depress antioxidant defenses, and by promoting mitochondrial impairment can increase free radical production. This shift in antioxidant defenses versus prooxidant forces might suffice to render some normally innocuous vaccines sufficiently prooxidant to produce symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Reactogenic vaccines are reported to produce oxidative stress [ 19 ]. Radiation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], as well as pesticides [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] (and solvents [ 52 , 53 ]), can depress antioxidant defenses, and by promoting mitochondrial impairment can increase free radical production. This shift in antioxidant defenses versus prooxidant forces might suffice to render some normally innocuous vaccines sufficiently prooxidant to produce symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies dealing with ELF‐MF effect on neuroendocrine system have been performed on pineal gland and hypothalamo‐pituitary‐gonadal axis (HPG). It has been shown that ELF‐MF changes serum levels of melatonin (Wilson, ; Dyche et al, ), prolactin, testosterone, luteinizing and follicle stimulating hormones (Margonato et al, ; Zecca et al, ; Al‐Akhras et al, ; Al‐Akhras, ; Ahangarpour et al, ). Results are not consistent probably due to different intensities and duration of exposure to ELF‐MF.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, Burchard et al 14 reported contradictory results between two replicates, whereas other studies 15 16 found no effect of ELFMF on MLT secretion in cows. No effect on the total day MLT but a significant difference in the day-night distribution was reported for mice 17 and a slightly increased MLT secretion was found in adult rats 18 . In humans, short-term studies with volunteers exposed to artificial magnetic fields mainly failed to demonstrate an effect on MLT levels while studies on populations living in the vicinity of strong ELF electric as well as magnetic fields hinted towards a disruptive effect on MLT secretion 5 .…”
mentioning
confidence: 75%